2016
DOI: 10.1088/0954-3899/43/4/045110
|View full text |Cite
|
Sign up to set email alerts
|

The12C* Hoyle state in the inelastic12C +12C reaction and in24Mg* decay

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…This is not the case for the (C + 3α) channel, and the anomalously high branching ratio of this channel can be tentatively attributed to a possible persistence at high excitation energy of α structure correlations in the 12 C+ 12 C molecular state and/or in the 24 Mg compound. The kinematic characteristics of these non-statistical decays are further studied in the continuation of this work [36].…”
Section: Discussionmentioning
confidence: 97%
“…This is not the case for the (C + 3α) channel, and the anomalously high branching ratio of this channel can be tentatively attributed to a possible persistence at high excitation energy of α structure correlations in the 12 C+ 12 C molecular state and/or in the 24 Mg compound. The kinematic characteristics of these non-statistical decays are further studied in the continuation of this work [36].…”
Section: Discussionmentioning
confidence: 97%
“…was obtained by Kirsebom et al by using the kinematic fitting method [29]. Two more recent experiments by Rana et al [30] and Morelli et al [31] suggested non-zero values of direct decay B.R., respectively of (Γ α − Γ α0 )/Γ α = 0.91% ± 0.14% and 1.1% ± 0.4%. Finally, thanks to a high statistics experiment, Itoh et al [32] determined an improved upper limit of the direct B.R.…”
mentioning
confidence: 92%
“…These characteristics make CsI(Tl) crystals particularly well-suited for being used as residual energy stages for silicon-based telescope systems, enabling the identification of fragments via the so-called ∆E-E technique [2]. Many large acceptance detection systems such as INDRA [3], CHIMERA [4,5], NIMROD-ISiS [6], GARFIELD [7] or FAZIA [8,9], have been used successfully in detecting and identifying particles in wide energy and mass ranges. Recently, detectors based on modular strip Si-CsI telescopes have been developed to provide high angular resolution in addition to high energy resolution for nuclear structure, particle-particle correlation and nuclear reaction studies.…”
Section: Introductionmentioning
confidence: 99%